2022
DOI: 10.3389/fpls.2022.854508
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptome Analysis Uncovers the Regulatory Roles of MicroRNAs Involved in Petal Color Change of Pink-Flowered Strawberry

Abstract: The pink-flowered strawberry is popular in China due to its high ornamental value. In the present study, sRNAome, transcriptome, and degradome sequencing were performed to understand the functions of microRNAs (miRNAs) and their target genes during flower development in pink-flowered strawberry. Nine small RNA libraries and a mixed degradome library from flower petals at different developmental stages were constructed and sequenced. A total of 739 known miRNAs and 964 novel miRNAs were identified via small RNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…The microRNAs (miRNAs) play important roles in plant growth, development, and response to stress [ 49 , 50 , 51 , 52 ]. It is indicated that miRNAs are also associated with petal color formation [ 53 , 54 ]. In the petals of strawberry ( Fragaria × ananassa ), it was found that the FamiRNA828a and FamiRNA858_R-2 were targeted by FaMYB114 and FaMYB308 , respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The microRNAs (miRNAs) play important roles in plant growth, development, and response to stress [ 49 , 50 , 51 , 52 ]. It is indicated that miRNAs are also associated with petal color formation [ 53 , 54 ]. In the petals of strawberry ( Fragaria × ananassa ), it was found that the FamiRNA828a and FamiRNA858_R-2 were targeted by FaMYB114 and FaMYB308 , respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In the petals of strawberry ( Fragaria × ananassa ), it was found that the FamiRNA828a and FamiRNA858_R-2 were targeted by FaMYB114 and FaMYB308 , respectively. For flower color intensity, this suggested that FamiR828a is negatively correlated with anthocyanin accumulation in pink-flowered strawberry petals [ 53 ]. It was also found that the mcr-miR858-MYB1/MYB5 and mcr-miR396- McCHI were involved in inhibiting anthocyanin synthesis in Malus crabapple [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…The over expression of miR828 in Arabidopsis showed light-colored leaf types, consistent with the phenotype of grape berries in controls, suggesting that miR828 acts as a repressor of anthocyanin biosynthesis [ 38 ]. A recent report stated that miR828 inhibits the intensity of petal color during the growth and development of pink strawberries [ 44 ]. Our results indicated that miR828 may be involved in the regulation of PA biosynthesis ( Figure 4 and Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Actually, there is an immense market potential for ornamental strawberries in the post-epidemic era (Guan et al, 2023). With a history of over 60 year efforts in modern ornamental strawberry breeding, breeders have successfully developed a broad assortment of pink-flowered and red-flowered strawberry cultivars with independent intellectual property rights (Mabberley, 2002;Khanizadeh et al, 2010;Xue et al, 2015;Ding et al, 2019;Bentvelsen and Vange, 2021;Yue et al, 2022;Guan et al, 2023). For instance, ABZ Seeds, a Dutch breeding company dedicated to the development of F1 hybrid seed-propagated strawberry cultivars, has delved into ornamental strawberry breeding and released a series of superior ornamental strawberry varieties full of aesthetic morphological attributes, such as "Summer Breeze Cherry Blossom", "Summer Breeze Rose", "Gasana" and "Toscana" in the market (Bentvelsen and Bouw, 2006;Bentvelsen and Vange, 2021).…”
Section: Strawberrymentioning
confidence: 99%